Implementation and Sustainability of a Pharmacy-Led, Hospital-Wide Bedside Medication Delivery Program: A Qualitative Process Evaluation Using RE-AIM - Prusaczyk, Beth; Mixon, Amanda S.; Kripalani, Sunil (Frontiers in Public Health, 2020)
Background: Few studies of hospital-based implementation assess sustainability or collect formal implementation outcomes, in part because the emphasis is often on initial adoption and rapid cycles of improvement. The purpose of this process evaluation was to assess the implementation of a pharmacy-led, hospital-wide program and contribute to the literature by collecting formal implementation outcomes, including sustainability. Methods: This was a qualitative process evaluation of a program that delivers discharge medications and related education to hospitalized patients' bedside prior to discharge. Semi-structured interviews were conducted with the program's key stakeholders to assess the program's implementation barriers and facilitators as well as its potential for sustainability. An interview guide was created based on the RE-AIM constructs of Reach, Adoption, Implementation, and Maintenance. Effectiveness was not assessed due to an ongoing effectiveness evaluation by another team. Each interview was coded by two independent coders and any discrepancy was adjudicated by a third, independent coder. Results: Twelve stakeholders were approached and all agreed to be interviewed. Related to providers' decisions to adopt the program, key themes emerged around the different priorities of nurses and physicians, which has implications for how program leadership promoted the program to these different stakeholder groups. Key implementation barriers included the nature of hospital provider rotations and turnover, which led to confusion on who could use the program and to whom providers should direct program-related questions. Key implementation facilitators included the enthusiasm of program staff and identified champions on the units. Themes related to maintenance or sustainability included the need to continually generate buy-in and educate providers about the program and allowing program staff and leadership to remain nimble and adapt their operations to meet evolving needs. Conclusions: The results suggest that in an environment in which rapidly achieving improvement is often the focus more than maintaining that improvement, strategies to achieve successful implementation may not be sufficient to achieve successful sustainment. New strategies are likely needed to address the unique barriers to sustaining a program once initial adoption and implementation is complete.